Sidik Jari DNA Plasma Nutfah Mangga Berdasarkan Analisis Fragmen Marka SSR (Simple Sequence Repeat) Berlabel - Dwinita W. Utami; Tri J. Santoso; N. Hidayatun (Jurnal Hortikultura Indonesia, 2012)
ABSTRACTDNA fingerprinting technology can be used for understanding the diversity of germplasm. The purpose of this preliminary study was to analyze the genetic diversity based on DNA fingerprints of mango germplasm using 15 fluorescent-labeled SSR markers. Nineteen Mango accessions from KP Cukurgondang collection, Pasuruan, East  Java and 15 SSR markers for mangoes  were used in this study. Development of  multiplex  sets of M13-labeled  primer  used  in the analysis  aimed  at  improving  the  effectiveness  and  efficiency  of molecular marker technology  in   mango  DNA  fingerprint  analysis.  The  analysis  of genetic  diversity  of  19  accessions  of  mango germplasm using 15 SSR markers resulted in 7 groups where four groups separated from the other three. Each of the four groups consisted of one accession, while the  three other groups consisted of some accessions. The results may represent the diversity of shape and color of fruit characters. However, further study is needed to get specific marker for each mango accession.Key word  : DNA fingerprint, Mango, fluorescent   SSR labeled.ABSTRAKTeknologi  sidik  jari  DNA  dapat  digunakan  untuk  memahami keanekaragaman  suatu  plasma nutfah.  Tujuan  dari  penelitian  awal  ini adalah  menganalisis  keragaman  genetik  berdasarkan  sidikjari DNA  plasma nutfah  mangga  menggunakan  15  marka  SSR  yang  berlabel  fluorescent. Sembilan  belas aksesi plasma nutfah mangga dari koleksi KP Cukurgondang, Pasuruan, JawaTimur dan 15 marka SSR untuk  mangga  digunakan  dalam penelitian  ini.  Pengembangan  set  multiplex  primer  berlabel  M13 digunakan dalam  analisis  bertujuan  untuk  meningkatkan  efektivitas  dan  efisiensi teknologi  marka molekuler dalam analisis sidikjari DNA mangga. Analisis keragaman genetik 19 aksesi plasma nutfah mangga menggunakan 15 marka SSR dapat menghasilkan 7 kelompok yang terdiri atas 4 kelompok yang masing-masing  beranggotakan  satu  aksesi  dan  3  kelompok  lainnya yang  terdiri  atas  beberapa  aksesi. Hasil  pengelompokan  dapat  mewakili keragaman  karakter  bentuk  dan  warna  buah.  Namun  demikian perlu dilakukan  analisis  lebih  lanjut  untuk  mendapatkan  penciri  spesifik  masing-masing  aksesi  plasma nutfah mangga.Kata kunci : Sidikjari DNA, mangga, SSR berlabel fluorescent